The lie tree - Hardinge, Frances (Amulet Books, 2016)
On an island off the south coast of Victorian England, fourteen-year-old Faith investigates the mysterious death of her father, who was involved in a scandal, and discovers a tree that feeds upon lies and gives those who eat its fruit visions of truth.